Corrosion mechanisms of pipelines with adjacent coating defects under AC interference: An interfacial process analysis - Lan, Wei; Wei, Biao; Li, Qianwei; Feng, Bo; Wang, Fuxiang; Bi, Wuxi; Liu, Daoqing (Materials & design, 2025)
[Display omitted] •A dual-cell device was designed to analyze AC-induced corrosion.•AC density does not affect the potential difference of adjacent coating defects.•The pH changes in the anode and cathode regions limited the corrosion process.•A mass transfer model was established to analyze AC corrosion. The corrosion process induced by AC (alternating current) stray currents poses a significant risk to the safe operation of buried pipelines. This study explores the interaction mechanism between anode and cathode regions formed by AC stray current at carbon steel coating defects. The results indicate that AC density does not affect the potential difference between defects. Furthermore, AC alters the interfacial pH characteristics, increasing the pH value in the anode region. Nernst-Plank equation was further used to analyze the mass transfer under AC. The AC field significantly impacts mass transfer at both the anode and cathode interfaces, creating steep concentration gradients of hydroxide and hydrogen ions near the surface regions of both electrodes. This phenomenon slows the negative shift of the anode corrosion potential (causing an increase in pH) while promoting a more pronounced negative shift of the cathode corrosion potential (resulting in a decrease in pH). Consequently, during AC stray current exposure, the anode and cathode corrosion reactions exhibit a dynamic shift in their electrochemical domains on the Pourbaix diagram. This work provides a reference for understanding the corrosion mechanism of AC-induced corrosion.